The steganoanalytical method for revealing a hidden communication channel with low capacity - Bobok, I.I. (Radiotekhnika, 2018)
Two stegano-analytical methods, CM1 and CM2, were developed. The basis of these methods is a new general approach to the problem of detecting integrity violations of digital images, which uses the properties of singular numbers and singular vectors of blocks of the image matrix. The proposed methods serve to identify the steganographic communication channel, formed by the Least Significant Bit method. A digital image in lossy format is used as a container. The methods CM1 and CM2 are effective for small values (less than 0.1 bit/pixel) of the latency channel capacity (LCC). Algorithms that implement methods are polynomial. Errors of the first kind are 1.7 and 1.3%, respectively, the errors of the second kind do not exceed 4% (LCC 0.01 bit/pixel). Existing modern analogues in conditions of such a small latency channel capacity do not work.